Unattended sensors in marine environments: oxybuoy for hypoxia study - Mohd Nor, Rizal; Nesterenko, Mikhail (IGI Global, 2016)
This chapter discusses the use of unattended sensors and its use in marine environment. The authors present challenges of designing a marine sensor in harsh environments and a case study in implement- ing a marine sensor to study hypoxia. Hypoxia is a world-wide anthropogenic phenomenon related to pollution. The authors describe the construction of an inexpensive sensor buoy system, Oxybuoy, de- signed for long-term unattended oxygen sensor measurements. The technology is available to construct such sensor buoys. The authors showed a prototype based on commercial off-the shelf components: an embedded PC, an optical dissolved oxygen sensor, a temperature sensor, a Wi-Fi transmitter and a satellite transmitter. Its total cost is around $5,000 to construct, program and test a proof of concept of such sensor. The authors describe the buoy’s architectural design and three experiments that the authors carried out to demonstrate its viability.